70.5k views
1 vote
Use mathematical induction to prove the statement is true for all positive integers n, or show why it is false. Picture attached.

Use mathematical induction to prove the statement is true for all positive integers-example-1

1 Answer

1 vote

True

1) There are three steps, to using mathematical induction.

2) The first one is to check for n=1


\begin{gathered} \left(3n-2\right)^2=(n\left(6n^2-3n-1\right))/(2) \\ \\ \left(3\cdot \:1-2\right)^2=(1\cdot \left(6\cdot \:1^2-3\cdot \:1-1\right))/(2) \\ \\ (3-2)^2=(1(6-3-1))/(2) \\ \\ 1^2=(2)/(2) \\ \\ 1=1\:\:True \end{gathered}

3) Secondly, let's prove it for n=k:


\sum _(k=1)^k\left(3k-2\right)^2=(k\left(6k^2-3k-1\right))/(2)

4) And finally, for n=k+1


\begin{gathered} \sum _(n=1)^n\left(3n-2\right)^2=(n\left(6n^2-3n-1\right))/(2) \\ \\ \sum _(\left(k+1\right)=1)^(k+1)\left(3\left(k+1\right)-2\right)^2=(\left(k+1\right)\left(6\left(k+1\right)^2-3\left(k+1\right)-1\right))/(2) \\ \\ \left(3\left(k+1\right)-2\right)^2+(k\left(6k^2-3k-1\right))/(2)=(\left(k+1\right)\left(6\left(k+1\right)^2-3\left(k+1\right)-1\right))/(2) \\ \\ 2\left(3\left(k+1\right)-2\right)^2+k\left(6k^2-3k-1\right)=\left(k+1\right)\left(6\left(k+1\right)^2-3\left(k+1\right)-1\right) \\ \\ 6k^3+15k^2+11k+2=6k^3+15k^2+11k+2 \\ \\ 6k^3+15k^2+11k+2-2=6k^3+15k^2+11k+2-2 \\ \\ 6k^3+15k^2+11k=6k^3+15k^2+11k \\ \\ 6k^3+15k^2+11k-\left(6k^3+15k^2+11k\right)=6k^3+15k^2+11k-\left(6k^3+15k^2+11k\right) \\ \\ 0=0 \\ \\ True. \end{gathered}

As all of those 3 steps were true. Then we can tell, that this is true.

User Itchydon
by
4.3k points